Content Analysis Kitab “Nubdzatul Bayan” Sebagai Buku Ajar Akselerasi Maharah Qiraah Di Ponpes Nurul Jadid - Rifqi Aulia Rahman; Efan Chairul Abdi; Chairani Astina; Lilik Rochmad Nurcholisho (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2023)
The research departs from the existence of the accelerated book 'Nubdzatul Bayan' which is used as an acceleration book for Qiraah proficiency at the Nurul Jadid Situbondo Islamic boarding school. This book with 6 volumes of Qawaid Arabic science content has made several Islamic boarding school students able to read Arabic texts in a short time. This research will focus on dissecting the contents of the six volumes of this book with the analysis knife of Willian Francis Mackey's learning theory with four principles, namely Selection, Gradation, Presentation, and Presentation. The research method that the writer uses is literature studies with the primary data being the book. Secondary data was obtained from several research journals and books. The conclusion from the content analysis of this textbook provides information about the purpose of the textbook, as well as the use of this Nubdzatul Bayan book in accordance with its learning outcomes, namely as a Qiraah proficiency acceleration book. The material presented helps determine the relevance of the textbook with the desired learning objectives. This study also provides information about the quality of the presentation of material that is systematic, clear, and easily understood by students. In conclusion, the content analysis of this textbook provides useful information for evaluating the effectiveness and efficiency of textbooks as learning aids. Thus, the analysis of the contents of textbooks becomes important in selecting and using the appropriate textbooks in accordance with the goals and needs of the students' Qiraah proficiency acceleration